Global characteristics and drivers of sodium and aluminum concentrations in freshly fallen plant litter - Wang, Yiqing; Wu, Fuzhong; Wu, Qiqian; Yue, Kai; Yuan, Ji; Yuan, Chaoxiang; Peng, Yan (Frontiers in Plant Science, 2023)
Plant litter is not only the major component of terrestrial ecosystem net productivity, the decomposition of which is also an important process for the returns of elements, including sodium (Na) and aluminum (Al), which can be beneficial or toxic for plant growth. However, to date, the global characteristics and driving factors of Na and Al concentrations in freshly fallen litter still remain elusive. Here, we evaluated the concentrations and drivers of litter Na and Al with 491 observations extracted from 116 publications across the globe. Results showed that (1) the average concentrations of Na in leaf, branch, root, stem, bark, and reproductive tissue (flowers and fruits) litter were 0.989, 0.891, 1.820, 0.500, 1.390, and 0.500 g/kg, respectively, and the concentrations of Al in leaf, branch, and root were 0.424, 0.200 and 1.540 g/kg, respectively. (2) mycorrhizal association significantly affected litter Na and Al concentration. The highest concentration of Na was found in litter from trees associated with both arbuscular mycorrhizal fungi (AM) and ectomycorrhizal fungi (ECM), followed by litter from trees with AM and ECM. Lifeform, taxonomic, and leaf form had significant impacts on the concentration of Na and Al in plant litter of different tissues. (3) leaf litter Na concentration was mainly driven by mycorrhizal association, leaf form and soil phosphorus concentration, while leaf litter Al concentration was mainly controlled by mycorrhizal association, leaf form and precipitation in the wettest month. Overall, our study clearly assessed the global patterns and influencing factors of litter Na and Al concentrations, which may help us to better understand their roles in the associated biogeochemical cycles in forest ecosystem.